Desain Balanced Scorecard Terintegrasi Dengan Pendekatan Six Sigma - Iman Supriadi (Jurnal Manajemen dan Inovasi (MANOVA), 2020)
The motivation behind this paper is to give new bits of knowledge into understanding the estimation of incorporating the Balanced Scorecard with Six Sigma. This paper depends on an exhaustive writing audit from BSC and Six Sigma. The writing survey gives the premise to another joining system dependent on the PDCA cycle. The discoveries of this paper show how coordinated frameworks can add further esteem contrasted with the autonomous execution of either BSC or Six Sigma. This investigation gives a structure that can fill in as a reason for the reconciliation of Six Sigma with BSC. This paper adopts another strategy to joining structures by recognizing purposes of incorporation influence through the qualities and shortcomings of BSC and Six Sigma. The fundamental commitment of this paper is that it gives new experiences into seeing how BSC can be coordinated with Six Sigma. In addition, this paper gives guidance for future research that will defeat shortcomings in the manner associations are coordinating BSC with Six Sigma today.